2022
DOI: 10.1007/jhep10(2022)064
|View full text |Cite
|
Sign up to set email alerts
|

On non-supersymmetric fixed points in five dimensions

Abstract: We generalize recent results regarding the phase space of the mass deformed E1 fixed point to a full class of five-dimensional superconformal field theories, known as X1,N. As in the E1 case, a phase transition occurs as a supersymmetry preserving and a supersymmetry breaking mass deformations are appropriately tuned. The order of such phase transition could not be unequivocally determined in the E1 case. For X1,N, instead, we can show that at large N there exists a regime where the phase transition is second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…. Moreover, very recently, the existence of five dimensional non-supersymmetric conformal field theories was investigated using several techiques, such as the ϵ-expansion, the bootstrap [36][37][38][39][40][41][42][43][44], and soft supersymmety breaking of known superconformal fixed points [45][46][47].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Moreover, very recently, the existence of five dimensional non-supersymmetric conformal field theories was investigated using several techiques, such as the ϵ-expansion, the bootstrap [36][37][38][39][40][41][42][43][44], and soft supersymmety breaking of known superconformal fixed points [45][46][47].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…This aspect becomes particularly useful when supersymmetry is softly broken and we lack control over the non-perturbative dynamics of the theory, as was observed recently for the E 1 theory subject to a soft SUSY breaking deformation [45]. It would be nice to perform a similar analysis on the X 1,N theory subject to the deformations studied in [47] and to see also if, as happens for the E 1 theory in this context [46], soft supersymmetry breaking deformations lead to instabilities on the Higgs branch of these theories. This is at the moment still work in progress.…”
Section: Jhep04(2024)148mentioning
confidence: 95%
See 2 more Smart Citations
“…The CFT capturing this phase transition would therefore be a UV completion of YM, and provide an example of a non-supersymmetric interacting CFT in d > 4. This scenario was further explored in [26], that showed that actually the phase transition should be viewed as separating the YM phase from a phase with spontaneous breaking of the instantonic JHEP04(2023)099 U (1), and in [48] where a certain generalization of the theory admitting a large N limit was argued to have a second order transition in that limit.…”
Section: F -Theorem In D =mentioning
confidence: 99%